INTEGRASI METODE SERVICE QUALITY (SERVQUAL), IMPORTANCE PERFORMANCE ANALYSIS (IPA), DAN MODEL KANO DALAM UPAYA PENINGKATAN KUALITAS PELAYANAN PADA MIVAS GALLERY BANYUWANGI - Roviqoh Fitama; Endang Suprihatin; Muhammad Yusuf (Journal of Industrial Engineering & Technology Innovation, 2026)
Mivas Gallery Banyuwangi is a tailoring service MSME that provides custom clothing production, garment alteration, school uniforms, and work uniforms. This study aims to evaluate service quality and determine service improvement priorities through the integration of Service quality (SERVQUAL), Importance Performance Analysis (IPA), and the Kano Model. A quantitative approach was employed involving 95 customers selected using a total sampling technique. The results of the validity and reliability tests indicated that the research instrument was suitable for data collection. SERVQUAL analysis showed that all service attributes had negative gap values, indicating that the perceived service performance had not fully met customer expectations. The largest gap was found in the order completion timeliness attribute with a value of -1.67. IPA results revealed that seven attributes were located in Quadrant I and became the main priorities for improvement. Meanwhile, the Kano Model classified service attributes into Must-Be, One-Dimensional, Attractive, and Indifferent categories. The integration results identified order completion timeliness, prompt WhatsApp response, and ease of tailoring revision as the highest-priority attributes for improvement. Therefore, focusing on these attributes is expected to enhance service quality and customer satisfaction sustainably.